Simulation video: a tool to evaluate communications skills in radiologist residents - Ding, Ning; Hu, Ge; Wang, Xuan; Sun, Hao; Song, Lan; Chen, Yu; Zhang, Daming; Xue, Huadan; Jin, Zhengyu (BMC medical education, 2023)
Background Effective communication is a crucial component of radiology resident training, and many different aspects need to be explored when teaching and evaluating communication skills. To ensure that radiology residents' communication skill levels can be measured accurately, a standardized evaluation tool has been introduced. In twenty hospitals in Beijing, simulation videos have been developed as a way to assess the communication skills of radiology residents during their certification exams, to minimize evaluating biases. This study aims to assess the performance of a simulation video model in evaluating communications skills compared to the standard patient model. Methods This is a retrospective observational study. The performance of standard patient and simulation video models was evaluated through an eight-year examination of communication skills in radiology residents. From 2014 to 2021, communications skill tests were administered to 1003 radiology residents in 20 hospitals in Beijing. The standardized patient (SP) model was applied in 2014, and simulation videos were used from 2015 to 2021. The difficulty and discrimination radio of the tests were evaluated. The subjective survey for candidates on two models of communication skills evaluation was performed and analyzed. Results The simulation video model evaluation demonstrated stable difficulty (ranging from 0.92 to 0.98) and discrimination ratio (ranging from 0.37 to 0.49), except for minor exceptions of discrimination in 2019 (0.58) and 2020 (0.20). Furthermore, the Kruskal-Wallis H test revealed no significant differences in average scores between 2016 (93.9 [+ or -] 4.6) and 2018 (94.5 [+ or -] 4.2), 2016 and 2019 (97.3 [+ or -] 3.9), 2017 (97.0 [+ or -] 5.6) and 2019, 2017 and 2020 (97.7 [+ or -] 4.7), as well as 2019 and 2020 exams (all p [greater than or equal to] 0.05). In addition, candidates who responded to the survey preferred the simulation video model (with a 77.2% response rate), with 62.7% choosing it over the SP model for communication skills evaluation. Conclusion The simulation video demonstrated a stable and better acceptable construct for assessing radiology residents' communication skills. Keywords: Communication skills, Radiology education, Evaluation model, Simulation video